HUBUNGAN ULKUS DIABETIK PADA PENDERITA DIABETES MELITUS DENGAN CITRA TUBUH DI PUSKESMAS UMBULSARI - Zahruddin; Khofi Hadidi (Jurnal Kesehatan dr. Soebandi, 2018)
Diabetic ulcers are the most feared complication of diabetes mellitus patients because the reduced blood supply to the tissue causes tissue death and is aggravated by bacterial infections that can cause amputation and even have wide impact because it can cause death, morbidity, increased treatment costs, and decreased quality of life. The incidence of foot ulcers in patients with diabetes mellitus is 1-4% and 10-30 times as much as foot ulcers causing the risk of amputation (toe, foot or lower leg). It is estimated that every year one million patients suffering from diabetic ulcers undergo amputation of the lower limb (85%) and a mortality rate of 15-40% annually and 39-80% every 5 years. The purpose of this study was to determine the relationship of diabetic ulcers in diabetics with body image at the Umbulsari Health Center. The research design used was analytic survey with coss sectional design. The sample in this study was taken by Probability Sample with a type of Consecutive Sampling that is a diabetic ulcer sufferer who performs an examination at Puskesmas Ambsari. This research was conducted by observing / observing the degree of injury for diabetic ulcers and questionnaire sheets for body image. The results of this study were analyzed using the statistical test Spearman rank test. The results of the analysis showed that first-degree injuries were 22 respondents (55%), second-degree injuries were 17 respondents (42.5%), and third-degree injuries were 1 respondent (2.5%). While the results of body image in people with diabetes mellitus as many as 13 respondents (32.5%) had a negative body image, while 27 respondents (67.5%) had a positive body image. The results of the analysis of the two variables obtained by the value of p value Sig. (two tailed) of 0.023 α α (0.05) which indicates that there is a relationship between diabetic ulcers in diabetics with the body image of the Umbulsari Health Center